Authentic oral interaction in the efl class: what it means, what it does not (2010)
The communicative approach in EFL education has generated a concern for the development of communication in the foreign language classroom within which the promotion of oral interaction is usually paramount. However, what constitutes authentic oral interaction is sometimes not clearly understood and some of the activities that take place in the classroom seem unlikely to generate meaningful opportunities for the development of oral interaction. To address this gap, this paper characterizes four samples of oral communication exchanges that occur in Colombian EFL secondary school classrooms in Montería and discusses their effectiveness for developing meaningful oral production in both student-student and teacher-student interaction. The paper has two main sections: the first is devoted to the analysis of student-student interaction, and the second to discussing teacherstudent exchanges. Key words: Oral interaction, English as a Foreign Language (EFL), oral production El enfoque comunicativo en la enseñanza del inglés como lengua extranjera ha generado una preocupación por el desarrollo de la comunicación en el aula de clases, en la cual se da gran importancia a la interacción oral. Sin embargo, aún se entiende poco lo que constituye la interacción oral auténtica y por ello las actividades de aprendizaje generan pocas oportunidades significativas para el desarrollo de la interacción oral. Por ello, el presente artículo caracteriza cuatro ejemplos de interacción oral comunes a las aulas de inglés de escuelas públicas de Montería, Colombia y discute su efectividad para desarrollar una producción oral significativa en la interacción estudiante-estudiante y profesor-estudiante. El artículo tiene dos secciones: la primera se encarga del análisis de la interacción estudiante-estudiante, la segunda discute la interacción profesor-estudiante. Palabras clave: interacción oral, inglés como lengua extranjera (ILE), producción oral